Tinjauan Motivasi Atlet Club Basket Black Hourse Squad Kota Lubuklinggau - Aprilia Nada Ramadina; Rudi Erwandi; Helvi Darsi (Silampari Jurnal Olahraga, 2021)
The purpose of this study was to determine how much the factors that influence the respondents' motivation in participating in the Black Hourse Squad basketball club in Lubuklinggau City. This research is a quantitative descriptive study using a survey method. The research subjects used were athletes or members of the Black Hourse Squad basketball club as many as 20 people. The instrument used in the form of a questionnaire to analyze the data used quantitative descriptive statistics with percentages. The results showed that the respondents' motivation in participating in the Black Hourse Squad basketball club in Lubuklingga City were mostly in the very high category with a frequency of 65%, followed by the high category with a frequency of 0%, then the low category with a frequency of 35%, and very low with a frequency of 0%. So it can be concluded that the motivation of the respondents in participating in the Black Hourse Squad basketball club of Lubuklinggau City is in the very high category as much as 65%.